2001
DOI: 10.1054/bjoc.2001.2084
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and inducible apoptosis in oesophageal adenocarcinoma

Abstract: The use of neoadjuvant chemoradiotherapy prior to surgery in the treatment of oesophageal adenocarcinoma has increased in recent years, and up to 25% of patients will have a complete pathological response to the neoadjuvant therapy. Many patients will not respond, however, and the knowledge of molecular factors predicting response or resistance to chemoradiotherapy is required to enhance treatment results. An understanding of apoptosis and cell proliferation may be relevant and this study focused on apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Despite variations in individual mechanisms of action, chemotherapy and radiotherapy ultimately bring about cancer cell death by activation of the apoptotic cascade 14,15 . In esophageal cancer, previous reports from this unit indicate that spontaneous apoptosis occurs in all cases of esophageal adenocarcinoma, that patients with a high apoptotic index have a better response to neoadjuvant therapy, and that apoptosis is significantly induced by chemoradiotherapy 16 . Regulators of apoptosis include p53, the Bcl‐2 protein family, and caspases, and these factors are implicated in the biology of chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite variations in individual mechanisms of action, chemotherapy and radiotherapy ultimately bring about cancer cell death by activation of the apoptotic cascade 14,15 . In esophageal cancer, previous reports from this unit indicate that spontaneous apoptosis occurs in all cases of esophageal adenocarcinoma, that patients with a high apoptotic index have a better response to neoadjuvant therapy, and that apoptosis is significantly induced by chemoradiotherapy 16 . Regulators of apoptosis include p53, the Bcl‐2 protein family, and caspases, and these factors are implicated in the biology of chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In a recent study, we reported that spontaneous apoptosis occurs in all cases of esophageal adenocarcinoma, that patients with a high apoptotic index have a better response to neoadjuvant therapy, and that apoptosis was significantly induced by chemoradiotherapy. 15 Overexpression of p53 had no regulatory role in the apoptotic process, nor did it predict sensitivity to neoadjuvant therapy, suggesting the existence of an alternate pathway that regulates this response. This study is an extension of this work and focuses on bcl-2, bax and bcl-x which are members of a family of genes (bcl-2 family) that function as regulators of apoptosis, with bcl-2 normally associated with an antiapoptotic function.…”
Section: Introductionmentioning
confidence: 97%
“…Apoptosis plays an important role in tumorigenesis and in the cytotoxic effects of chemotherapy and radiation therapy 13,14 . In a recent study, we reported that spontaneous apoptosis occurs in all cases of esophageal adenocarcinoma, that patients with a high apoptotic index have a better response to neoadjuvant therapy, and that apoptosis was significantly induced by chemoradiotherapy 15 . Overexpression of p53 had no regulatory role in the apoptotic process, nor did it predict sensitivity to neoadjuvant therapy, suggesting the existence of an alternate pathway that regulates this response.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is an important pathway of cell death following radiotherapy, chemotherapy, and apoptotic gene therapy in cancers, including esophageal cancer (6)(7)(8). A major mode of resistance to antitumor therapy, including radiotherapy and chemotherapy, is insensitivity to apoptosis induction (9).…”
Section: Introductionmentioning
confidence: 99%